Special modified asphalt mixture for low-carbon aging-resistant ultrathin overlay and preparation method of special modified asphalt mixture

By adopting special modified asphalt mixture with low-carbon aging resistance and ultra-thin covers, and using solid waste materials such as waste tires, steel slag and bagasse, the existing asphalt cover technology has insufficient durability, poor anti-slip effect, low environmental protection and high engineering costs, and achieved cost-effective preventive maintenance effects on the road surface.

CN119874256APending Publication Date: 2025-04-25GUANGXI TRANSPORTATION SCI & TECH GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510035564.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing asphalt cover technology has insufficient durability, poor anti-slip effect, low environmental protection and high engineering costs.

Method used

The special modified asphalt mixture with low-carbon aging resistance and ultra-thin cover is adopted, including special modified asphalt, steel slag aggregate, mineral powder, anti-flaking agent and bagasse fiber. Through fine formulation and processing technology, the durability and anti-slip properties of the mixture are improved.

Benefits of technology

It significantly improves the environmental protection and durability of the mixture, reduces engineering costs, and achieves cost-effective road surface preventive maintenance effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874256A_ABST
    Figure CN119874256A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt, in particular to a special modified asphalt mixture for a low-carbon anti-aging ultrathin overlay and a preparation method, and the special modified asphalt mixture comprises the following components in parts by weight: 4.6-5.4 parts of special modified asphalt, 88-94 parts of steel slag aggregate, 1-4 parts of mineral powder, 0.1-0.3 part of an anti-stripping agent and 0.5-1.8 parts of bagasse fiber. The special modified asphalt is prepared from the following components in parts by weight: 62 to 86 parts of matrix asphalt, 6 to 20 parts of rubber powder, 2 to 10 parts of a high-viscosity agent, 0.3 to 3 parts of a reinforcing agent, 0.1 to 0.3 part of a cross-linking agent, 0.6 to 4.2 parts of a stabilizer, 2 to 8 parts of an accelerant, 1 to 5 parts of a viscosity reducer and 0.1 to 4 parts of an anti-aging agent. The rubber-based special modified asphalt suitable for the ultrathin overlay and the mixture thereof are researched and developed, so that the environmental protection property and durability are remarkably improved, a solution is provided for flexible traffic infrastructure construction and carbon-to-peak carbon neutralization development goals, and the problems of insufficient durability, poor anti-skid effect, low environmental protection property and high engineering cost of the existing asphalt overlay technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt, in particular to a special modified asphalt mixture of a low-carbon, aging-resistant and ultra-thin overlay and a preparation method thereof. Background Art

[0002] my country's highways have entered a stage of development with equal emphasis on construction and maintenance. Early road diseases such as pavement skid resistance attenuation, minor cracks, spalling and particle loss, and push rutting are relatively common, seriously affecting the service life of the road surface and increasing the cost of project maintenance. There is an urgent need to develop a cost-effective preventive pavement maintenance technology that can "cure multiple diseases at the same time."

[0003] Asphalt overlay technology is currently a hot preventive maintenance direction for solving the above-mentioned problems. Many road researchers have carried out research and application practices on various types of ultra-thin overlays such as hot mix and cold mix, and have accumulated many technical achievements.

[0004] Commonly used ultra-thin covers often require the use of epoxy polymer binders, which are expensive and have strict construction requirements. They have poor weather resistance under the coupling of heat, oxygen and load. Technical measures such as micro-surfacing and fog sealing have insufficient durability and poor anti-slip effects. Traditional ultra-thin covers generally use high-quality aggregates, asphalt and other raw materials, which fully guarantee performance. However, they consume a large amount of hard and wear-resistant stones such as basalt and diabase. Under the increasingly tense "sand and gravel shortage" conditions, resources are scarce and costs have increased significantly. Under the guidance of the dual-carbon development goals, large industrial and agricultural solid waste materials such as waste tires, steel slag, and bagasse have become important factors restricting energy conservation, emission reduction and carbon reduction, and their stock and utilization rate are not high. Summary of the invention

[0005] The purpose of the present invention is to provide a special modified asphalt mixture and a preparation method for a low-carbon, aging-resistant, ultra-thin overlay, aiming to solve the problems of existing asphalt overlay technology such as insufficient durability, poor anti-skid effect, low environmental protection and high engineering cost.

[0006] To achieve the above-mentioned purpose, in the first aspect, the present invention provides a special modified asphalt mixture for a low-carbon, aging-resistant, ultra-thin overlay, which comprises 4.6-5.4 parts of special modified asphalt, 88-94 parts of steel slag aggregate, 1-4 parts of mineral powder, 0.1-0.3 parts of anti-stripping agent and 0.5-1.8 parts of bagasse fiber, calculated by the total weight of 100 parts; the special modified asphalt comprises 62-86 parts of base asphalt, 6-20 parts of rubber powder, 2-10 parts of high viscosity agent, 0.3-3 parts of reinforcing agent, 0.1-0.3 parts of cross-linking agent, 0.6-4.2 parts of stabilizer, 2-8 parts of accelerator, 1-5 parts of viscosity reducer and 0.1-4 parts of anti-aging agent, calculated by the total weight of 100 parts.

[0007] Among them, the special modified asphalt mixture of the low-carbon, aging-resistant and ultra-thin cover has a void ratio of 4%-6%, a Marshall strength of >10kN, a dynamic stability of >8000 times / mm, a residual stability of >90%, a low-temperature bending strain of >3000με, a water permeability coefficient of 0-80ml / min, a structural depth of 0.6-1.4mm, and a pendulum friction coefficient of 60-86BPN.

[0008] In a second aspect, the present invention further provides a method for preparing a special modified asphalt mixture with a low-carbon, aging-resistant, ultra-thin surface, which is used to prepare the special modified asphalt mixture with a low-carbon, aging-resistant, ultra-thin surface as described in the first aspect, and is characterized in that it comprises the following steps:

[0009] Preparation of special modified asphalt based on special modified asphalt raw materials;

[0010] Preheating the steel slag aggregate and the special modified asphalt, adding the preheated steel slag aggregate and bagasse fiber into a stirring container, and stirring for 60 seconds to obtain a primary mixture;

[0011] A preset amount of the special modified asphalt is added to the primary mixture, stirred for 60 seconds, and then a preset amount of mineral powder and an anti-stripping agent are added, and dry-mixed for 60 seconds to obtain a special modified asphalt mixture with a low-carbon, aging-resistant and ultra-thin surface.

[0012] The specific method for preparing special modified asphalt based on special modified asphalt raw materials is as follows:

[0013] Heat the base asphalt to 175°C and maintain the temperature for 1.5 hours;

[0014] Adding rubber powder, high viscosity agent and reinforcing agent to the heated base asphalt respectively, stirring and swelling, and high-speed shearing to obtain a primary swelling product;

[0015] Adding a viscosity reducer, a promoter and a stabilizer to the swollen product respectively, and shearing at high speed to obtain a secondary modified product;

[0016] Then add the cross-linking agent, stir and develop to obtain special modified asphalt.

[0017] Wherein, the preheating temperature of the steel slag aggregate is 190°C, and the preheating temperature of the special modified asphalt is 175°C.

[0018] The special modified asphalt mixture of the low-carbon anti-aging ultra-thin overlay of the present invention comprises 4.6-5.4 parts of special modified asphalt, 88-94 parts of steel slag aggregate, 1-4 parts of mineral powder, 0.1-0.3 parts of anti-stripping agent and 0.5-1.8 parts of bagasse fiber, calculated by the total weight of 100 parts, and the special modified asphalt comprises 62-86 parts of base asphalt, 6-20 parts of rubber powder, 2-10 parts of high viscosity agent, 0.3-3 parts of reinforcing agent, 0.1-0.3 parts of crosslinking agent, 0.6-4.2 parts of stabilizer, 100 parts of accelerator, 0.5-1.8 parts of slag fiber, 0.6-20 parts of rubber powder, 0.5-1.8 parts of slag fiber, 0.5-1.8 parts of slag fiber, 0.5-1.8 parts of slag fiber, 0.6-20 parts of slag fiber, 0.5-1.8 ... 2-8 parts of agent, 1-5 parts of viscosity reducer and 0.1-4 parts of anti-aging agent. This special modified asphalt mixture comprehensively utilizes solid waste materials such as waste tires, steel slag, bagasse, etc. to develop rubber-based special modified asphalt suitable for ultra-thin overlays and its mixture, which significantly improves environmental protection and durability, and provides solutions for the construction of resilient transportation infrastructure and the development goals of carbon peak and carbon neutrality. At the asphalt binder level, the rubber powder processed from waste tires is used as a modifier; at the mixture level, solid waste steel slag is used as aggregate, and bagasse fiber developed from waste bagasse is used as an additive. This can effectively absorb industrial and agricultural solid waste materials such as waste tires, steel slag, and bagasse, realize high-value resource utilization, and reduce carbon emissions. The rubber-based special asphalt used contains carbon black and has high resistance to UV aging. In addition, bagasse fiber plays a good reinforcement role, significantly improving the high temperature, low temperature, and water damage resistance of the mixture, thereby ensuring durability. The mechanical strength and wear resistance of steel slag aggregate are more prominent than traditional limestone, basalt, and diabase, which can provide long-lasting anti-skid performance and ensure safety in use. Rubber powder is a highly elastic material that can play a good role in shock absorption and noise reduction in ultra-thin covers, improving driving comfort. Solid waste materials are generally low in cost, so the overall cost of the ultra-thin cover can be reduced, achieving the goal of high cost performance, and solving the problems of insufficient durability, poor anti-skid effect, low environmental protection, and high engineering cost of existing asphalt cover technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 The present invention provides a flow chart of a method for preparing a special modified asphalt mixture for a low-carbon, ageing-resistant, ultra-thin overlay.

[0021] Figure 2 It is a flow chart of the specific method for preparing special modified asphalt based on special modified asphalt raw materials. DETAILED DESCRIPTION

[0022] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0023] In the first aspect, the present invention provides a special modified asphalt mixture for a low-carbon, aging-resistant, ultra-thin overlay, which comprises 4.6-5.4 parts of special modified asphalt, 88-94 parts of steel slag aggregate, 1-4 parts of mineral powder, 0.1-0.3 parts of anti-stripping agent and 0.5-1.8 parts of bagasse fiber, based on a total of 100 parts by weight. The special modified asphalt comprises 62-86 parts of base asphalt, 6-20 parts of rubber powder, 2-10 parts of high viscosity agent, 0.3-3 parts of reinforcing agent, 0.1-0.3 parts of cross-linking agent, 0.6-4.2 parts of stabilizer, 2-8 parts of promoter, 1-5 parts of viscosity reducer and 0.1-4 parts of anti-aging agent, based on a total of 100 parts by weight.

[0024] In an embodiment of the present invention, the special modified asphalt mixture of the low-carbon, aging-resistant and ultra-thin cover has a void ratio of 4%-6%, a Marshall strength of >10kN, a dynamic stability of >8000 times / mm, a residual stability of >90%, a low-temperature bending strain of >3000με, a water permeability coefficient of 0-80ml / min, a structural depth of 0.6-1.4mm, and a pendulum friction coefficient of 60-86BPN.

[0025] This special modified asphalt mixture comprehensively utilizes solid waste materials such as waste tires, steel slag, and bagasse to develop rubber-based special modified asphalt and its mixture suitable for ultra-thin overlays, which significantly improves environmental protection and durability, and provides solutions for the construction of resilient transportation infrastructure and the development goals of carbon peak and carbon neutrality. At the asphalt binder level, rubber powder processed from waste tires is used as a modifier; at the mixture level, solid waste steel slag is used as aggregate, and bagasse fiber developed from waste bagasse is used as an additive. In this way, industrial and agricultural solid waste materials such as waste tires, steel slag, and bagasse are effectively consumed, high-value resource utilization is achieved, and carbon emissions are reduced. The rubber-based special asphalt used contains carbon black and has high resistance to ultraviolet aging. In addition, bagasse fiber plays a good reinforcement role, significantly improving the high temperature, low temperature, and water damage resistance of the mixture, thereby ensuring durability. The mechanical strength and wear resistance of steel slag aggregate are more prominent than those of traditional limestone, basalt, and diabase, which can provide long-lasting anti-skid performance and ensure safety in use. Rubber powder is a highly elastic material that can play a good role in shock absorption and noise reduction in ultra-thin overlays, improving driving comfort. Solid waste materials are generally low in cost, so the overall cost of the ultra-thin overlay can be reduced, achieving the goal of high cost performance, and solving the problems of insufficient durability and poor anti-skid effect of existing asphalt overlay technology.

[0026] Among them, the base asphalt is selected from 50#, 70#, 90# and other road petroleum asphalt according to the use environment and driving load conditions; the rubber powder can be processed from heavy-duty truck tires, family car tires, sole rubber, etc., with a fineness of 30-120 mesh. According to whether the desulfurization process is adopted, it is divided into ordinary rubber powder and activated rubber powder; the high viscosity agent can significantly increase the dynamic viscosity at a temperature threshold of 40-80°C, but will not significantly increase the viscosity of asphalt at a high temperature threshold of 160°C and above. The high viscosity agent can be prefabricated with the base asphalt into a wet-process rubber-based special modified asphalt, or it can be added by dry direct casting in the preparation of asphalt mixture.

[0027] The reinforcing agent can be a linear or star-shaped styrene-butadiene-styrene block copolymer, or a compound polystyrene-butadiene copolymer, which can significantly enhance the high-temperature deformation resistance, low-temperature ductility and other properties of asphalt; the viscosity reducer is a gel-like elastomer, which is composed of one or more of organic acids, stearic acid, polyvinyl alcohol, organic wax, surfactants, etc., and can quickly reduce the viscosity of rubber-based special modified asphalt at temperatures of 150°C and above, but does not affect the viscosity of asphalt at temperatures of 100°C and below.

[0028] The accelerator can be one or more complexes of cycloalkyl rubber oil, aromatic oil, etc., which can effectively promote the dissolution between rubber powder and materials such as matrix asphalt, and is conducive to the compatibility between complex materials and components; the cross-linking agent is mainly used in the high-temperature preparation process. The rubber powder has a certain desulfurization and depolymerization, and the small molecule products increase, which is not conducive to the cross-linking stability of the rubber asphalt system and is prone to precipitation and segregation. The cross-linking agent re-links the small molecules to build a stable cross-linked structure of rubber asphalt; the stabilizer is a nanomaterial treated with surface activity (a nano-composite inorganic powder material treated with activity), which increases the surface activity of the nanomaterial, thereby improving the organic combination between rubber particles and asphalt molecules, enhancing the molecular interface force, promoting the uniform dispersion, strong adsorption and compatibility of rubber particles, and improving the stability of rubber asphalt. The steel slag aggregate is derived from the by-product of the steelmaking process. The pressure hot stuffing method or rolling method is used to effectively control the free calcium oxide content and improve the stability. The steel slag aggregates with different particle sizes such as 0-3mm, 3-5mm, 5-8mm and 5-10mm are mainly used. Generally, in order to ensure better adhesion performance, 0-3mm limestone fine aggregate can be used instead; the bagasse fiber comes from the waste of the sugar industry, and is made through screening, soaking, shearing dispersion and chemical modification. The fiber length is within 6mm, the oil absorption rate is 5-9 times, and the mass loss is less than 6%; the bagasse fiber can also be granulated, and the granulation medium is preferably asphalt-based material, which can ensure better dispersion when preparing asphalt mixture.

[0029] See also Figure 1 to Figure 2 In a second aspect, the present invention further provides a method for preparing a special modified asphalt mixture with a low-carbon, aging-resistant, ultra-thin surface, which is used to prepare the special modified asphalt mixture with a low-carbon, aging-resistant, ultra-thin surface as described in the first aspect, and is characterized in that it comprises the following steps:

[0030] S1 prepares special modified asphalt based on special modified asphalt raw materials;

[0031] Specific method:

[0032] S11: heating the base asphalt to 175°C and maintaining the temperature for 1.5 hours;

[0033] In an embodiment of the present invention, the matrix asphalt is heated to 175°C and the temperature is maintained for not less than 1.5 hours. During the process, it is stirred once every 15 minutes with a glass rod, a steel rod, etc. to ensure that the matrix asphalt is heated evenly.

[0034] S12: adding rubber powder, high viscosity agent and reinforcing agent to the heated base asphalt respectively, stirring and swelling, and high-speed shearing to obtain a primary swelling product;

[0035] In an embodiment of the present invention, rubber powder, high viscosity agent and reinforcing agent are respectively added to the base asphalt, stirred and swelled at 500-800 rpm for 15-30 min, and high-speed shearing is performed at 5000 rpm for 10-30 min (temperature is controlled at 170-185°C) using a high-speed shearing machine.

[0036] S13: adding a viscosity reducer, a promoter and a stabilizer to the swollen product respectively, and shearing at a high speed to obtain a secondary modified product.

[0037] In an embodiment of the present invention, a viscosity reducer, a promoter, and a stabilizer are respectively added to the swelling material, and a high-speed shearing machine is used for high-speed shearing at 5000 rpm for 5-20 min (temperature is controlled at 170-185°C), and then a cross-linking agent is added in S14, stirred and grown to obtain a special modified asphalt.

[0038] In the embodiment of the present invention, a cross-linking agent is added, and the mixture is stirred at 500-800 rpm for 70-100 min (temperature is controlled at 170-185° C.) to prepare a rubber-based special modified asphalt.

[0039] S2 preheats the steel slag aggregate and the special modified asphalt, adds the preheated steel slag aggregate and bagasse fiber into a stirring container, and stirs for 60 seconds to obtain a primary mixture;

[0040] In the embodiment of the present invention, the preheating temperature of the steel slag aggregate is 190° C., the preheating temperature of the special modified asphalt is 175° C., the steel slag aggregate and the special modified asphalt are preheated at the above-mentioned proposed temperature for no less than 4 hours, and the stirring container is preheated at 175° C. First, each level of steel slag aggregate or limestone aggregate and bagasse fiber are added to the stirring container and stirred for 60 seconds.

[0041] S3: adding a preset amount of the special modified asphalt to the primary mixture and stirring for 60 seconds to obtain a secondary mixture.

[0042] S4 then adds a preset amount of mineral powder and anti-stripping agent, and dry mixes for 60 seconds to obtain a special modified asphalt mixture with a low-carbon, aging-resistant, ultra-thin surface.

[0043] In order to better understand the present technical solution, the following embodiments are provided for further explanation:

[0044] Embodiment 1:

[0045] Formula of rubber-based special modified asphalt material: 78 parts of 70# base asphalt, 6 parts of ordinary rubber powder, 6 parts of high viscosity agent, 1.5 parts of enhancer, 0.2 parts of cross-linking agent, 1.5 parts of stabilizer, 3.8 parts of accelerator, 3 parts of viscosity reducer, and 0 parts of antioxidant.

[0046] Preparation method ①: After the base asphalt is heated to 175℃, add rubber powder, high viscosity agent and reinforcing agent and stir evenly, and stir and swell for 15 minutes. Use a high-speed shearing machine to high-speed shear for 15 minutes at 5000 rpm (temperature controlled at 170℃), add viscosity reducer, accelerator and stabilizer and high-speed shear for 10 minutes, then add cross-linking agent and stir and develop for 70 minutes (temperature controlled at 175℃).

[0047] Preparation method ②: After the base asphalt is heated to 175°C, add rubber powder, high viscosity agent and reinforcing agent and stir evenly, and stir and swell for 20 minutes. Use a high-speed shearing machine to high-speed shear for 20 minutes at 5000 rpm (temperature controlled at 175°C), add viscosity reducer, accelerator and stabilizer and high-speed shear for 10 minutes, then add cross-linking agent and stir and develop for 80 minutes (temperature controlled at 175°C).

[0048] Preparation method ③: After the base asphalt is heated to 175°C, add rubber powder, high viscosity agent and reinforcing agent and stir evenly, and stir and swell for 30 minutes. Use a high-speed shearing machine to high-speed shear for 30 minutes at 5000 rpm (temperature controlled at 180°C), add viscosity reducer, accelerator and stabilizer and high-speed shear for 20 minutes, then add cross-linking agent and stir and develop for 90 minutes (temperature controlled at 180°C).

[0049] Preparation method ④: After the base asphalt is heated to 175°C, add rubber powder, high viscosity agent and reinforcing agent and stir evenly, and stir and swell for 30 minutes. Stir at 800 rpm for 30 minutes (temperature controlled at 180°C), add viscosity reducer, accelerator and stabilizer and stir for 20 minutes, then add cross-linking agent and stir for 90 minutes (temperature controlled at 180°C).

[0050]

[0051] According to the test results of four different preparation methods, it can be seen that the rubber asphalt prepared by pure mixing process is relatively the worst, especially in terms of low softening point and ductility, high Brookfield viscosity, and low dynamic viscosity, which is significantly lower than the composite preparation process of mixing + high-speed shearing. The main reason is that under the shearing, grinding, and crushing of the high-speed shearing machine, the rubber powder and other additives can be accelerated from large particles to fine particles, and the macromolecular substances can be cracked into small molecules, which promotes the homogenization of the asphalt mortar system. By comparing preparation methods ①-③, it can be seen that with the extension of swelling development time, high-speed shearing time and processing temperature, the performance indicators of rubber-based special modified asphalt are continuously improved. The performance indicators of preparation method ③ are the best, with a softening point close to 90℃, an ductility of more than 20cm, a dynamic viscosity of more than 300,000 Pa.s, and a Brookfield viscosity that can be controlled within 2Pa.s. The process conditions of preparation method ③ are optimal and can be used as the process method for subsequent comparative tests.

[0052] Embodiment 2:

[0053] Based on the formula of Example 1 and the mass of 70# matrix asphalt, the cross-linking agent, stabilizer, accelerator, viscosity reducer and anti-aging agent are converted to the external admixture ratio of 70# matrix asphalt and remain unchanged. Rubber powder, high viscosity agent and reinforcing agent are taken as three variable factors, and the external admixture ratio of 70# matrix asphalt is also used. A 3-factor 4-level orthogonal experiment is set. The orthogonal experiment design is shown in the following table.

[0054]

[0055]

[0056] The rubber-based modified asphalt was prepared according to the above formula and key index tests were carried out. The results are shown in the table.

[0057]

[0058] According to the results of the orthogonal test, it can be seen that the higher the rubber powder content, the smaller the needle penetration and ductility, the softening point and dynamic viscosity do not change significantly, and the Brookfield viscosity increases. The higher the reinforcing agent content, the less obvious changes in needle penetration, Brookfield viscosity, and dynamic viscosity, and the greater the softening point and ductility. The higher the high viscosity content, the less obvious changes in needle penetration and Brookfield viscosity, the higher the softening point and ductility, and the significantly improved dynamic viscosity. When formulating materials, the performance indicators and cost control goals can be combined for optimization. It is recommended to use 12% external rubber powder, 2% reinforcing agent, and 8% high viscosity agent, which is equivalent to 75 parts of internal 70# matrix asphalt, 9 parts of ordinary rubber powder, 6 parts of high viscosity agent, 2 parts of reinforcing agent, 0.2 parts of cross-linking agent, 1.5 parts of stabilizer, 3.8 parts of accelerator, 3 parts of viscosity reducer, and 0 parts of anti-aging agent.

[0059] Embodiment 3:

[0060] Based on the formula recommended in Example 2, the amount of the cross-linking agent was changed to 0.1 part, 0.2 part, and 0.3 part, respectively, and the corresponding base asphalt was 75.1 parts, 75 parts, and 74.9 parts. The remaining materials were the same as the formula recommended in Example 2, respectively recorded as Scheme 2-1, 2-2, and 2-3. The processing technology adopted preparation method ③, and the test results of the three schemes of Example 2 were obtained as follows:

[0061]

[0062] According to the test results, the penetration decreases with the increase of cross-linking agent, while the softening point and Brookfield viscosity increase, and the ductility and dynamic viscosity show a trend of increasing first and then decreasing. It can be seen from the aging test technical indicators that the penetration ratio and ductility of Scheme 2-2 are better, indicating that it has better aging resistance. Comprehensive comparison shows that the indicators of Scheme 2-2 are better, so the recommended dosage of the cross-linking agent is 0.2 parts.

[0063] Embodiment 4:

[0064] The rubber-based special modified asphalt is prepared according to the preferred scheme recommended in Example 2, and the ultra-thin overlay asphalt mixture is prepared according to the following material composition: 62 parts of 5-10mm steel slag aggregate, 8 parts of 3-5mm steel slag aggregate, 23 parts of 0-3mm limestone aggregate, 2 parts of mineral powder, 0.2 parts of bagasse fiber, and 4.8 parts of rubber-based special modified asphalt.

[0065] Preparation method: The oven temperature of steel slag aggregate is 190℃, the temperature of rubber-based special modified asphalt is 175℃, and it is preheated for no less than 4h according to the above-mentioned proposed temperature, and the mixing container is preheated to 175℃. First, add various grades of steel slag aggregate or limestone aggregate and bagasse fiber into the mixing container and stir for 60s; add the rubber-based special modified asphalt according to the preset amount and stir for 60s; finally, add the preset amount of mineral powder and dry mix for 60s. The rubber-based special modified asphalt mixture can be prepared, and Marshall specimens, rutting plate specimens, etc. can be made according to the performance indicators required for the test.

[0066] The Marshall stability, residual stability, freeze-thaw splitting strength, dynamic stability, structural depth, pendulum friction coefficient and other indicators of the rubber-based special modified asphalt mixture were tested, and the results are shown in the following table.

[0067]

[0068] At present, the types of asphalt used for ultra-thin asphalt overlays mainly include SBS modified asphalt, high-viscosity modified asphalt, rubber modified asphalt, etc., as well as the rubber-based special modified asphalt provided by the present invention. The technical indicators of three samples of original asphalt, TFOT aging, and heat-oxygen-ultraviolet light coupled aging were tested, and the results are shown in the following table.

[0069]

[0070] It can be seen that compared with the original asphalt, the softening point and ductility are ranked as high viscosity modified asphalt > SBS modified asphalt > rubber-based special modified asphalt > rubber modified asphalt; the 60°C dynamic viscosity is ranked as rubber-based special modified asphalt > high viscosity modified asphalt > rubber modified asphalt > SBS modified asphalt.

[0071] Comparing the asphalt after TFOT aging, the penetration ratio is ranked as follows: rubber-based special modified asphalt > high viscosity modified asphalt > SBS modified asphalt = rubber modified asphalt; the ductility ratio is ranked as follows: rubber-based special modified asphalt > rubber modified asphalt > SBS modified asphalt > high viscosity modified asphalt.

[0072] Comparing the asphalt after heat-oxygen-UV coupled aging, the penetration ratio is ranked as follows: rubber-based special modified asphalt > high viscosity modified asphalt > rubber modified asphalt > SBS modified asphalt; the ductility ratio is ranked as follows: rubber-based special modified asphalt > rubber modified asphalt > SBS modified asphalt > high viscosity modified asphalt.

[0073] In summary, it can be seen that after TFOT aging and heat-oxygen-UV coupled aging, the penetration ratio and elongation ratio of rubber-based special modified asphalt are the best, indicating that rubber-based special modified asphalt has better aging resistance.

[0074] (2) The above four types of asphalt, namely SBS modified asphalt, high viscosity modified asphalt, rubber modified asphalt and rubber-based special modified asphalt, were used to prepare the preferred steel slag asphalt mixture, and the specimens were subjected to heat-oxygen-ultraviolet light coupled aging to test the technical indicators of the asphalt mixture. The results are shown in the following table.

[0075]

[0076] Compared with the original asphalt mixture, the Marshall stability is ranked as high viscosity modified asphalt mixture > rubber-based special modified asphalt mixture > rubber modified asphalt mixture > SBS modified asphalt mixture; the residual stability, freeze-thaw splitting strength and dynamic stability are ranked as high viscosity modified asphalt mixture > rubber-based special modified asphalt mixture > rubber modified asphalt mixture > SBS modified asphalt mixture; the low temperature bending strain and four-point bending fatigue life are ranked as high viscosity modified asphalt mixture > rubber-based special modified asphalt mixture > SBS modified asphalt mixture > rubber modified asphalt mixture; the structural depth of the four asphalts is basically equivalent, and the pendulum friction coefficient is ranked as rubber modified asphalt mixture > rubber-based special modified asphalt mixture > high viscosity modified asphalt mixture > SBS modified asphalt mixture.

[0077] Comparing the asphalt mixtures after heat-oxygen-ultraviolet light coupled aging, the ranking of residual stability is rubber-modified asphalt mixture > rubber-based special modified asphalt mixture > high viscosity modified asphalt mixture > SBS modified asphalt mixture; the ranking of freeze-thaw splitting strength is rubber-based special modified asphalt mixture > rubber-modified asphalt mixture > high viscosity modified asphalt mixture > SBS modified asphalt mixture; the ranking of dynamic stability is high viscosity modified asphalt mixture > rubber-based special modified asphalt mixture > rubber-modified asphalt mixture > SBS modified asphalt mixture; the ranking of low-temperature bending strain ratio and four-point bending fatigue life ratio is rubber-based special modified asphalt mixture > rubber-modified asphalt mixture > high viscosity modified asphalt mixture > SBS modified asphalt mixture.

[0078] In summary, it can be seen that in the comparison of various road performances of the original asphalt mixture, the high-viscosity modified asphalt mixture is the best, followed by the rubber-based special modified asphalt mixture. After heat-oxygen-ultraviolet light coupled aging, it was found that the rubber-based special modified asphalt mixture had the smallest attenuation in key indicators such as water stability, low temperature performance, and fatigue performance, showing better anti-aging durability.

[0079] What is disclosed above is only a preferred embodiment of the special modified asphalt mixture and preparation method for the low-carbon, aging-resistant, ultra-thin overlay of the present invention. Of course, it cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. Low-carbon, aging-resistant, ultra-thin surface special modified asphalt mixture, characterized by ; The special modified asphalt, calculated based on the total weight of 100 parts, includes 4.6-5.4 parts of special modified asphalt, 88-94 parts of steel slag aggregate, 1-4 parts of mineral powder, 0.1-0.3 parts of anti-stripping agent and 0.5-1.8 parts of bagasse fiber. The special modified asphalt, calculated based on the total weight of 100 parts, includes 62-86 parts of base asphalt, 6-20 parts of rubber powder, 2-10 parts of high viscosity agent, 0.3-3 parts of reinforcing agent, 0.1-0.3 parts of cross-linking agent, 0.6-4.2 parts of stabilizer, 2-8 parts of accelerator, 1-5 parts of viscosity reducer and 0.1-4 parts of anti-aging agent.

2. The special modified asphalt mixture with low carbon, aging-resistant and ultra-thin surface as claimed in claim 1, characterized in that; The special modified asphalt mixture of the low-carbon, aging-resistant and ultra-thin cover has a void ratio of 4%-6%, a Marshall strength of >10kN, a dynamic stability of >8000 times / mm, a residual stability of >90%, a low-temperature bending strain of >3000με, a water permeability coefficient of 0-80ml / min, a structural depth of 0.6-1.4mm, and a pendulum friction coefficient of 60-86BPN.

3. A method for preparing a special modified asphalt mixture for a low-carbon, aging-resistant, ultra-thin overlay, which is used to prepare the special modified asphalt mixture for a low-carbon, aging-resistant, ultra-thin overlay as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: Preparation of special modified asphalt based on special modified asphalt raw materials; Preheating the steel slag aggregate and the special modified asphalt, adding the preheated steel slag aggregate and bagasse fiber into a stirring container, and stirring for 60 seconds to obtain a primary mixture; Adding a preset amount of the special modified asphalt to the primary mixture and stirring for 60 seconds to obtain a secondary mixture; Then add a preset amount of mineral powder and anti-stripping agent, dry mix for 60 seconds, and obtain a special modified asphalt mixture with a low-carbon, aging-resistant and ultra-thin surface.

4. The method for preparing the special modified asphalt mixture with low carbon aging resistance and ultra-thin overlay as claimed in claim 3, It is characterized by: The specific method for preparing special modified asphalt based on special modified asphalt raw materials is: Heat the base asphalt to 175°C and maintain the temperature for 1.5 hours; Adding rubber powder, high viscosity agent and reinforcing agent to the heated base asphalt respectively, stirring and swelling, and high-speed shearing to obtain a primary swelling product; Adding a viscosity reducer, a promoter and a stabilizer to the swollen product respectively, and shearing at high speed to obtain a secondary modified product; Then add the cross-linking agent, stir and develop to obtain special modified asphalt.

5. The method for preparing a special modified asphalt mixture with low-carbon, aging-resistant and ultra-thin overlay as claimed in claim 1, characterized in that; The preheating temperature of the steel slag aggregate is 190°C, and the preheating temperature of the special modified asphalt is 175°C.

Citation Information

Patent Citations

  • Crack-resistant wearing layer asphalt mixture and preparation method thereof

    CN103265227A

  • Modified asphalt material and preparation method thereof

    CN110564168A

  • Ultra-thin anti-skid wear material based on steel slag aggregate and application of ultra-thin anti-skid wear material

    CN113582587A

  • Steel slag anti-skid wearing layer asphalt mixture and preparation method thereof

    CN115650639A

  • Ultrathin overlay composite modified asphalt for heavy traffic and preparation method thereof

    CN117402504A